2008
DOI: 10.2967/jnumed.107.049437
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine Therapy and Graves' Ophthalmopathy

Abstract: Appearances of and increases in Graves' ophthalmopathy (GO) have been reported after treatment of patients with hyperthyroidism with radioiodine. We sought to determine the rates of appearance or increase in manifestations of GO in American patients treated with radioiodine for hyperthyroidism. Methods: The study population, which consisted of 76 patients (range, 10.6-72 y), included 61 women and individuals of diverse ethnicity. The patients were followed for 1 y after radioiodine treatment. The clinical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…However, the difference between both groups did not remain significant, likely because our study was not designed and powered enough to specifically address this question. It is now well established that worsening of GO may occur after RAI administration [6,7,8,9], but there is no clear consensus about the need for prophylactic use of glucocorticoids when RAI has to be given to patients with preexisting GO [25,26]. Some advocate steroid administration only in the presence of risk factors such as smoking, high TSI levels, severe preexisting GO or high levels of FT 3 before treatment [8,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference between both groups did not remain significant, likely because our study was not designed and powered enough to specifically address this question. It is now well established that worsening of GO may occur after RAI administration [6,7,8,9], but there is no clear consensus about the need for prophylactic use of glucocorticoids when RAI has to be given to patients with preexisting GO [25,26]. Some advocate steroid administration only in the presence of risk factors such as smoking, high TSI levels, severe preexisting GO or high levels of FT 3 before treatment [8,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, its use is limited by the potential risk of development or worsening of Graves' ophthalmopathy (GO) following therapy. While several reports did not demonstrate progression of GO following RAI (1,2), many more found a significant association between RAI and the development or the worsening of preexisting GO, including one systematic review (3)(4)(5)(6)(7). GO progression after RAI is more likely to occur in patients who already have GO prior to therapy, smoke, have severe hyperthyroidism, high levels of thyrotropin receptor antibody (TRAb), short duration of disease, or whose post-RAI hypothyroidism is not promptly corrected by levothyroxine replacement therapy (8,9).…”
Section: Introductionmentioning
confidence: 95%
“…24 Another group used the full 10-item CAS and designated an increase of 2 points as progression. 23 Träisk et al 17 used their own ''Clinical TAO Assessment Score'' with TAO points from 0 to 3 in chemosis, eyelid edema, redness, Hertel increase, impaired eye movement, corneal involvement, and visual impairment. A number of studies simply stated application of NOSPECS 12,19,22,38 and others described the components of the full ophthalmological evaluation.…”
Section: Other Considerationsmentioning
confidence: 99%
“…The total change in CAS scores over the 1-year period was insignificant, however, and authors concluded that there is no evidence of progression of TAO attributable to RAI. 23 Subsequent studies included direct comparison with antithyroid medications. El-Kaissi et al 24 published a prospective study wherein no evidence of new occurrence or progression of TAO was found by CAS and MRI in 24 post-RAI patients compared with carbimazole-treated patients, despite significantly elevated TSH levels post-RAI.…”
Section: ' Rai Does Not Worsen Thyroid Eye Diseasementioning
confidence: 99%